Diversity of endophytic bacteria in mulberry (Morus spp.) scions with different genetic resources - Zhang, Yun-fei; Qin, Ying-ting; Liu, Ze-yu; Zheng, Hao-ran; Hu, Xu-dong; Wang, Xi-ling (Frontiers in Microbiology, 2025)
Endophytic bacteria in plants play crucial roles in promoting plant growth, facilitating nutrient acquisition, and enhancing stress tolerance. Although many studies have recently investigated endophytic bacteria in plants, the characteristics of endophytic bacterial communities in germplasm resource populations have rarely been reported. In this study, we investigated the endophytic bacterial communities of 21 mulberry scions, representing both wild and cultivated resources, all grafted onto a common rootstock and grown under identical cultivation conditions. High-throughput sequencing of 16S rRNA amplicons was performed using the Illumina MiSeq platform. The results revealed a total of 10 phyla, 31 classes, 50 orders, 50 families, and 113 genera of endophytic bacteria in the mulberry scions. The dominant phylum was Proteobacteria (89.07%), followed by Firmicutes (5.20%) and Actinobacteria (3.10%). At the genus level, Sphingomonas (32.84%), Methylobacterium-Methylorubrum (18.64%), and Aureimonas (8.76%) were the predominant genera enriched in the scion. Wild scions exhibited more complex endophytic bacterial communities compared to cultivated scions. Among the wild germplasm, XZBS and XZMK, originating from Tibet, China, displayed distinctive Actinobacteria signatures, suggesting a potential legacy of primitive geographic adaptation. Co-occurrence network analysis indicated that Sphingomonas and Methylobacterium-Methylorubrum acted as keystone taxa, forming critical bridges within the endophytic bacterial community network in the scions. Functional predictions further indicated that endophytic bacteria from wild species showed a greater metabolic capacity for aromatic compounds, amino acids, and carbohydrates compared with those from cultivated species. Moreover, analyses of the mulberry genetic population structure and endophytic bacterial community composition suggested that differentiation between wild and cultivated resources was associated with differences in endophytic bacterial communities. This study provides new insights into the diversity of endophytic bacteria among different mulberry germplasm resources and highlights geographically unique taxa, advancing our understanding of microbiome-driven adaptation in perennial grafted plants. It also offers a valuable reference for the future utilization of functional endophytic bacteria in mulberry improvement.